The Scale of Agricultural Production in the United States - Black, J. D.; Allen, R. H.; Negaard, O. A. (Quarterly Journal of Economics, 1939)
Measures of size, 330. — Historical trends, 331. — Geographic differences in the size pattern, 334. — Size according to type of farming, 336. — Shifts between size groups, 339. — Proportion of total land and product in different size groups, 341. — Regional differences in concentration, 344. — Historical trends for selected counties, 348. — Hypotheses, 352. — How size of farms is determined, 355. — Variations in size with same area, 360. — Large-scale farming in the United States, 361. — The rôle of small and middle-sized farms, 366. —Summary of conclusions, 369.